2020
DOI: 10.1038/s41598-020-63360-6
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Size Effect on the Electrical Properties of Monolayer Graphene based Interconnects for Next Generation MQCA based Nanoelectronics

Abstract: Graphene interconnects have been projected to out-perform Copper interconnects in the next generation Magnetic Quantum-dot Cellular Automata (MQCA) based nano-electronic applications. In this paper a simple two-step lithography process for patterning CVD monolayer graphene on SiO 2 /Si substrate has been used that resulted in the current density of one order higher magnitude as compared to the state-of-the-art graphene-based interconnects. Electrical performances of the fabricated graphene interconnects were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 44 publications
(68 reference statements)
1
18
0
Order By: Relevance
“…Controlling the sheet size is crucial to obtain higher electrical conductivity. It has been shown that the electrical conductivity of graphene paper depends on the precursor GO sheet size and larger GO sheets led to higher electrical conductivity for the final graphene paper. ,, The mechanism behind this phenomenon is the lower intersheet contact resistance in the graphene paper containing larger GO (and hence rGO) sheets. Figure shows TEM, SEM, and AFM images of EEG sheet synthesized with (NH 4 ) 2 SO 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Controlling the sheet size is crucial to obtain higher electrical conductivity. It has been shown that the electrical conductivity of graphene paper depends on the precursor GO sheet size and larger GO sheets led to higher electrical conductivity for the final graphene paper. ,, The mechanism behind this phenomenon is the lower intersheet contact resistance in the graphene paper containing larger GO (and hence rGO) sheets. Figure shows TEM, SEM, and AFM images of EEG sheet synthesized with (NH 4 ) 2 SO 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Currently, it attracts a growing research interest due to its unique properties, including structure (the theoretical value of the specific surface area is 2630 m 2 g −1 ), rigidity (Young’s modulus is approximately 1100 GPa) and strength (the fracture strength is about 125 GPa). Furthermore, it has a very high electrical current density (at the level of 108 Acm −2 ) and mobility of charge carriers (2 × 10 5 cm 2 V −1 s −1 ) [ 1 , 2 , 3 , 4 ]. Its thermal conductivity depends on the direction of heat propagation and reaches a value of 3000 Wm −1 K −1 in the parallel direction and 5 Wm −1 K −1 in the perpendicular direction to the sample surface [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is huge interest in the thermal properties of twodimensional (2D) materials, motivated by applications to thermal management [1][2][3][4], interconnects in integrated circuits [5][6][7], thermoelectric devices [8][9][10][11] and nanoscale fabrication [12][13][14][15]. While nanoscale constrictions are of great importance for their electrical transport characteristics, particularly in the quantum regime [16,17], they also promote enhanced Joule self-heating and thermoelectric coefficients [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The nanowire and bow tie are excellent representative examples because they exhibit markedly different behaviour: the electrical resistances of the nanowire and bow tie have different dependences on the width w, and this means that Joule heating is independent of w for the nanowire (for small w and (4). Light grey indicates two leads at temperature T 0 with boundary condition (5), dark grey indicates insulating regions with boundary condition (6). Cartesian coordinate axes (x, y) are shown in (a) with the origin O at the centre of the sample.…”
Section: Introductionmentioning
confidence: 99%